The Association between Serum Malondialdehyde and Nitric Oxide Level of Children Living In Area of Chronic Pesticide Exposure - Astra Parahita; Galuh Hardaningsih; Anindita Soetadji (Diponegoro International Medical Journal, 2020)
Background: Chronic exposure of organophosphate pesticides is an oxidative stress that causes liver and aortic damage. Malondialdehyde (MDA) is a biological marker of oxidative damage to cell lipids membrane. The liver produces insulin growth factor-1 (IGF-1) which stimulates the enzyme nitric oxide synthase (eNOS) to produce vascular nitric oxide (NO). Children who are living in those area may be exposed to pesticide chronically. Objective: The study aims is to determine the relationship between serum MDA and NO level of children living in an area of chronic pesticide exposure.Method: Cross sectional study was conducted to 50 children aged between 8 – 10 years in agriculture areas of Brebes. Serum MDA and NO level was measured at the same time using ELISA method, data were shown on numerical scale. Statistical analysisby Pearson correlation.Result: Fifty children met the criteria, consisting of 30 males (60%) and 20 females (40%). The mean of serum MDA level in males, females, and total subjects were normal 6.03 (3.86) µg/ mL, 5.18 (2.11) µg/ mL, and 5.69 (2.60) µg/ mL, respectively. The mean of serum NO level in males, females, and total subjects were increased 79.42 (50.78) µmol/ L, 68.11 (50.81) µmol/ L, and 74.90 (50.58) µmol/ L, respectively. There was no association between serum MDA and NO level found.Conclusion: Serum NO level of children living in an area of chronic pesticide exposure was higher than normal value. However, there was no association between serum MDA and NO level found.